Effectiveness Level of Regional Original Revenue, Urban Buffer, and Rural Areas - M. Fajar Novriansyah; Maulana Mukhlis; Pitojo Budiono; Syarief Makhya (Universitas Medan Area, 2021)
This study aims to analyze and determine the level of effectiveness of regional revenue. The study was conducted in Bandar Lampung City, Pringsewu Regency, and Mesuji Regency. This study used secondary data, which were analyzed by quantitative descriptive method. Secondary data were obtained from the regional budget reports for Bandar Lampung City, Pringsewu Regency, and Mesuji Regency, which had been processed and analyzed. To solve this problem, use the effectiveness ratio formula in analyzing the effectiveness of regional revenue receipts. The results in this study indicate that the level of effectiveness of regional original revenue (PAD) in Bandar Lampung City, Pringsewu Regency and Mesuji Regency in 2016-2019 was fluctuating. Pringsewu Regency and Mesuji Regency had an average regional original revenue effectiveness ratio in the last four years, including the effective category, while Bandar Lampung City in the last four years was in the less effective category. This study concludes that the effectiveness of regional revenue in Bandar Lampung City, Pringsewu Regency, and Mesuji Regency has an unstable regional original revenue since it has increased and decreased. The effectiveness level does not affect the contribution given to regional revenue.